A methodology to forecast some attributes of an automatic storyteller's outputs. Issue 1 (2nd January 2020) - Guerrero Román, Iván; Pérez y Pérez, Rafael
ABSTRACT: This paper reports an extension of the program MEXICA, an automatic plot generator. The purpose of this project is to build a framework that permits studying the relations between MEXICA's processes, its knowledge structures and the features of the produced narratives. We describe a methodology to analyse the features of the agent's knowledge-base, to further establish correlations between such features and a set of general characteristics of the tales that they produce. Next, we make use of those correlations to forecast some properties of the future tales to be developed by different MEXICAs agents with different knowledge-bases. For this task, we introduce the S-graphs, representations of the similarity and organisation of the knowledge-structures. The results we obtained indicate that we are able to correctly forecast some of the features of tales to be produced; however, much more work is required.